THE FIRST YEARS OF PUTIN'S REIGN: RUSSIAN-EURO-ATLANTIC RELATIONS OF COOPERATION AND PARTNERSHIP - Blagojević, Jelisaveta (Political Review, 2024)
This paper aims to indicate the period of development of relations of cooperation and joint action between Russia and its Euro-Atlantic allies. It is about the beginning of Vladimir Putin's rule, whose basic foreign policy idea was the harmonization of two processes: providing the most favorable international environment to achieve the internal stabilization of the country and its economic recovery, and the renewal of Russian influence in international relations, primarily in Europe and its neighborhood. The new beginning of relations was marked by Putin's expression of solidarity and announcement of support to the United States of America after the terrorist attack of September 11, 2001, then the opening of the NATO Information Office in Moscow, the adoption of the Action Plan for the fight against terrorism, as well as the establishment of the NATO–Russia Council. However, after August 2008 and the Russian military action in Georgia, Russian-Euro-Atlantic relations started to get cold. This information is presented through the analysis of the content of the available literature and documentation as well as the application of the historiographical method of analysis, whereby the conclusion was drawn that moves and steps in international relations are determined by the internal economic, military, and overall stability of the actors.
Keywords: Putin; NATO; Russia; terrorism; United States of America